Rancang Bangun Alat Pendeteksi Keaslian Batu Bacan Doko Berbasis Mikrokontroler ATMega2560 - Alhamid, Umar Djafar; Prambodo, Yoga Listi; Asruddin, Asruddin (Sistem Komputer dan Teknologi Intelegensi Artifisial (SIKOMTIA), 2023)
This research designed and developed a tool to detect the authenticity of Bacan Doko. The development of this tool uses TCS3200 sensor components as a detection of color variations in stones, BH1750 sensors to measure light intensity, and LCD1602 to display information on stone detection results visually. This study aims to overcome the problem of identifying the authenticity of Bacan Doko stones which are often difficult to detect accurately by ordinary people who do not understand the world of gemology, which results in the existence of fake stones on the market. The presence of this tool provides innovation in the world of gemology by utilizing microcontroller and sensor technology to overcome the authentication problem of Bacan Doko stone accurately, and support the integrity of the gemstone market. The development of data processing algorithms is carried out to analyze and process information received from input values on sensors. The detection tool provides good results to recognize and distinguish genuine Bacan Doko stones based on the color characteristics of the sensor identification results TCS3200 taking into account the light intensity measured by the BH1750 sensor and information can be displayed clearly through the LCD screen. The development of this tool successfully proved its effectiveness in identifying the authenticity of Bacan Doko stone. This tool can be a reliable solution for traders and gemstone observers in ensuring the authenticity of Bacan Doko.